Transient Acute Kidney Injury (AKI) is common following significant kidney hypoperfusion - Md Ralib, Azrina; Pickering, John W.; Shaw, Geoffrey M.; Thann, Martin; Endre, Zoltan H. (Wiley-Blackwell Publishing, 2012)
Aim: To investigate transient early acute kidney injury (AKI) that occur in high risk patients.